2007
DOI: 10.1111/j.1479-828x.2007.00713.x
|View full text |Cite
|
Sign up to set email alerts
|

Getting an evidence‐based post‐partum haemorrhage policy into practice

Abstract: Greater assistance is needed to ensure that hospitals have the capacity to develop a policy applicable to local needs. Maternity hospitals throughout the state provide different levels of care and NSW DoH policy directives should not be 'one size fits all' documents. Earlier recognition of PPH may be facilitated by routine post-partum monitoring of all women and should be consistent throughout the state, regardless of hospital level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
3

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 9 publications
1
14
0
3
Order By: Relevance
“…We hope that other institutions will take the data presented here, along with the resources that are readily available from other online sources 20,28 and produce hemorrhage response systems that will be tailored to their facility. Based on the success of the protocol presented here and reported elsewhere, 27,28,[36][37][38][39] the primary goals of those endeavors should include (1) enhanced communication with all members of the hospital who may be part of the treatment team, (2) on-going staff education regarding key elements of the protocol. (3) blood loss assessment training, (4) standardized treatment that changes as the acuity of the patient changes and prevents repeated use of ineffective intervention, (5) early requirement for physician (obstetric and anesthesia) bedside assessment, and (6) early intervention with fixed ratios of blood products.…”
Section: Commentmentioning
confidence: 99%
“…We hope that other institutions will take the data presented here, along with the resources that are readily available from other online sources 20,28 and produce hemorrhage response systems that will be tailored to their facility. Based on the success of the protocol presented here and reported elsewhere, 27,28,[36][37][38][39] the primary goals of those endeavors should include (1) enhanced communication with all members of the hospital who may be part of the treatment team, (2) on-going staff education regarding key elements of the protocol. (3) blood loss assessment training, (4) standardized treatment that changes as the acuity of the patient changes and prevents repeated use of ineffective intervention, (5) early requirement for physician (obstetric and anesthesia) bedside assessment, and (6) early intervention with fixed ratios of blood products.…”
Section: Commentmentioning
confidence: 99%
“…A total of nine references that addressed the issue of postpartum hemorrhage management in a survey format were identified. None of the identified references addressed the national trends of postpartum management in the United States and only one of the references dealt with current evidence-based practice and recommendations [22]. Therefore, we conducted a survey developed by one of the authors (MJP) of a national sample of obstetricians (OB/GYNs) to describe the current treatment strategies relative to postpartum hemorrhage.…”
Section: Methodsmentioning
confidence: 99%
“…Cameron et al concluded in his study that Postpartum Hemorrhage is a potentially lifethreatening complication of childbirth occurring in up to 10% of birth. 8 Shamoona from Federal Government Services Hospital, Islamabad, reported a frequency of 3.7%-8.6%. 9 Roohi et al showed frequency of 13% in her study done in Punjab Medical College and its affiliated hospital Faisalabad.…”
Section: Discussionmentioning
confidence: 99%